2021
DOI: 10.1136/neurintsurg-2021-017742
|View full text |Cite
|
Sign up to set email alerts
|

Thrombectomy for secondary distal, medium vessel occlusions of the posterior circulation: seeking complete reperfusion

Abstract: BackgroundWhether to approach distal occlusions endovascularly or not in medium-sized vessels secondary to proximal large vessel occlusion stroke remains unanswered.ObjectiveTo investigates the technical feasibility and safety of thrombectomy for secondary posterior circulation distal, medium vessel occlusions (DMVO).MethodsTOPMOST (Treatment fOr Primary Medium vessel Occlusion STroke) is an international, retrospective, multicenter, observational registry of patients treated for distal cerebral artery occlusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…There are many reports in the literature of vessel movement and straightening during thrombectomy ( 30 , 31 ). There have also been reports of vessel movement and rupture of perforators when treating more distal occlusions due to the higher fragility of these vessels and looser attachment to the parenchyma ( 32 , 33 ). Thus, a thrombectomy manoeuvre may displace an entire arterial segment, increasing the risk of perforators detaching from the main trunk.…”
Section: Characteristics Of Current In-vitro Modelsmentioning
confidence: 99%
“…There are many reports in the literature of vessel movement and straightening during thrombectomy ( 30 , 31 ). There have also been reports of vessel movement and rupture of perforators when treating more distal occlusions due to the higher fragility of these vessels and looser attachment to the parenchyma ( 32 , 33 ). Thus, a thrombectomy manoeuvre may displace an entire arterial segment, increasing the risk of perforators detaching from the main trunk.…”
Section: Characteristics Of Current In-vitro Modelsmentioning
confidence: 99%
“…Accurate prediction of perfusion outcome may help in the selection of patients for e.g. intra-arterial thrombolysis [35,36] administration of antithrombotics [37,38] or secondary distal MT [39,40]. While potentially beneficial, all of these treatments also harbor a risk of harm, warranting a careful patient selection.…”
Section: Potential Role Of Ivt As Rescue Treatmentmentioning
confidence: 99%
“…In addition, a recent retrospective study on posterior circulation thrombectomy revealed frequent evidence of distal migration even pre-procedurally similar to what we report. 14 This study identified seven cases that presented as an isolated VA occlusion and received alteplase. Detrimental TM was seen in two out of seven patients.…”
Section: Thrombus Migration Casementioning
confidence: 99%